2013
DOI: 10.1590/1414-431x20122559
|View full text |Cite
|
Sign up to set email alerts
|

Leptin receptor (Ob-R) mRNA expression and serum leptin concentration in patients with colorectal and metastatic colorectal cancer

Abstract: The objective of the present study was to investigate the effect of leptin on the progression of colorectal carcinoma to metastatic disease by analyzing the serum leptin concentration and Ob-R gene expression in colon cancer tissues. Tissue samples were obtained from 31 patients who underwent surgical resection for colon (18 cases) and metastatic colon (13 cases) cancer. Serum leptin concentration was determined by an enzyme-linked immunosorbent assay (ELISA) and Ob-R mRNA expression by real-time polymerase ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 20 publications
(29 reference statements)
0
18
0
Order By: Relevance
“…It is noteworthy that a positive correlation was observed among leptin, Ob-R, VEGF, and microvessel density (MVD) in colorectal carcinoma [117]. In accordance with the protein expression (i.e., Ob-R) in tumor tissue that has been discussed above, Erkasap et al documented higher mRNA expression of Ob-R in metastatic growth compared to primary colorectal cancer [119]. …”
Section: Leptin and Tumor Behavior Of The Gastrointestinal Tractmentioning
confidence: 85%
See 1 more Smart Citation
“…It is noteworthy that a positive correlation was observed among leptin, Ob-R, VEGF, and microvessel density (MVD) in colorectal carcinoma [117]. In accordance with the protein expression (i.e., Ob-R) in tumor tissue that has been discussed above, Erkasap et al documented higher mRNA expression of Ob-R in metastatic growth compared to primary colorectal cancer [119]. …”
Section: Leptin and Tumor Behavior Of The Gastrointestinal Tractmentioning
confidence: 85%
“…Similar to colon cancer [119], metastases from ovarian cancers were found to have higher Ob-Rb expression than what was associated with primary tumors [16]. In vitro studies with various ovarian cancer cell-lines further demonstrated that leptin stimulated cell migration and invasion.…”
Section: Female Reproductive System Cancersmentioning
confidence: 99%
“…A positive association has been found between obesity and the risk for the development of various cancers, among them colorectal cancer (CRC) [1, 2]. Several mechanisms have been proposed to explain this association: chronic inflammation, excess production of leptin [3] (concomitantly with an onset of systemic resistance to leptin signaling [4]) and decreased adiponectin secretion in obese subjects, which may deregulate cellular growth and angiogenesis, and therefore promote cancer development and progression [58]. …”
Section: Introductionmentioning
confidence: 99%
“…A growing body of evidence indicates that the metabolic syndrome (MetS) and expression of various adipokines (leptin and adiponectin) associated with obesity plays a crucial role in the development of colorectal cancer (Hardwick et al, 2001;Hoda et al, 2007;Endo et al, 2011;Aleksandrova et al, 2012;Healy et al, 2012;Erkasap et al, 2013;Gialamas et al, 2013). In obese people, the elevated insulin level, the rapidly growing secretion of leptin, and decreased adiponectin levels altogether activate several signaling pathways that favor carcinogenesis and are associated with colon cancer development.…”
Section: Obesity-leptin and Adiponectinmentioning
confidence: 99%
“…In vitro studies clearly demonstrated that abnormal leptin expression in human colon epithelial cells functions as a growth factor. Leptin or its soluble receptor (ObRb) acts at various stages of neoplastic progression and at stages subsequent to tumor initiation in CRC cell lines (Endo et al, 2011;Erkasap et al, 2013). Moreover, Paik et al (2009) documented that leptin expression increased gradually in the normal-adenoma-adenocarcinoma sequence of CRC development and promoted their proliferation.…”
Section: Obesity-leptin and Adiponectinmentioning
confidence: 99%